The Effect of Hypnosis on The Level of Anniversity of Women With HIV/AIDS - Hesti Wiji Utami; Wiwin Mintarsih (Midwifery and Nursing Research, 2021)
Background: The level of anxiety of women with HIV / AIDS has different categories for each individual, the main cause of this anxiety is hopelessness to depression due to the diagnosis obtained. A person's level of anxiety can be overcome by various methods, one of which is hypnosis. Hypnosis is a natural method used to relieve fear, panic, tension and mental stress. Hypnosis is carried out by direct contact with a person's subconscious mind, giving positive suggestions so that a person can build a positive emotional state. The purpose of this study was to determine the effect of hypnosis on the level of anxiety of women with HIV / AIDS in Tasikmalaya City in 2019.Methods: This type of research is included in experimental research with a quantitative approach. The design of this research is Pre-Experimental Design with One Group Pretest-Posttest Design. The population was 19 people with the total sampling technique of 19 people. The data analysis technique used the Wilcoxon Test.Results: The results of this study found that the anxiety level of women with HIV / AIDS before hypnosis was at a moderate level of anxiety. After hypnosis, most of the anxiety levels were in the mild category. The Wilcoxon test results, the value is less than a (0.001 0.05), so it shows that there is an effect of hypnosis on the anxiety level of women with HIV / AIDS. The results of this study found that the anxiety level of women with HIV / AIDS before hypnosis was at a moderate level of anxiety. After hypnosis, most of the anxiety levels were in the mild category. The Wilcoxon test results, the value is less than a (0.001 0.05), so it shows that there is an effect of hypnosis on the anxiety level of women with HIV / AIDS.Conclusion: the anxiety level of women with HIV / AIDS before hypnosis was at a moderate level of anxiety. After hypnosis, most of the anxiety levels were in the mild category. The Wilcoxon test results, the value is less than a (0.001 0.05), so it shows that there is an effect of hypnosis on the anxiety level of women with HIV / AIDS